D-Dimer Levels as a Predictor of Clinical Outcome and Mortality in Acute Ischemic Stroke Patients: A Systematic Review and Meta-Analysis - Pearl Dhodik Wirasman; Abdulloh Machin; Jenar Harumi (AKSONA, 2023)
Highlight: An increase in the D-dimer level indicates activation of the coagulation system through thrombus formation and fibrinolysis. The meta-analysis found a significant relationship between elevated d-dimer levels and worsening clinical outcomes and increased mortality. The D-dimer level can be used as a predictor for predicting clinical outcomes and mortality in acute ischemic stroke patients at each duration of follow-up.   ABSTRACT Introduction: In ischemic stroke, high D-dimer levels are frequently found, indicating coagulation with ongoing thrombus formation and fibrinolysis. Objective: The purpose of this study was to analyze the role of D-dimer in predicting clinical outcomes and mortality in acute ischemic stroke patients. Methods: A systematic literature search was conducted using the PRISMA method through the PubMed, Science Direct, and Google Scholar databases. The quality of the article was assessed using the Newcastle-Ottawa Scale (NOS) and statistically analyzed using Review Manager software version 5.4.1. Results: Eight articles had good quality according to NOS and matched the criteria for the literature search. Elevated D-dimer levels and worsened clinical outcomes have a significant result when discharged from the hospital: OR 2.37 (95% CI 1.68–3.35); I2 = 45% p < 0.00001; 1-month: OR 1.75 (95% CI 1.38–2.23), I2 = 47% p < 0.00001; 3-months: OR 2.43 (95% CI 2.00–2.95), I2 0% p < 0.00001; 6-months: OR 2.64 (95% CI 1.92–3.63), I2 = 0% p < 0.00001; and 12-months: OR 1.92 (95% CI 1.31–2.82), I2 = 62% p < 0.0008. Elevated D-dimer level and increased mortality have a significant result with OR 2.25 (95% CI 1.78–2.85), I2 = 45% p < 0.00001. Conclusion: D-dimer can be used as a predictor of clinical outcome and mortality in acute ischemic stroke.